Cross-Cultural issues at Icelandic workplaces - Aya Arakaki 1982- (2013)
This study investigates current situation of multiculturalism at workplaces in Iceland. 46 foreign workers and 36 Icelandic workers at various organizations answered the online questionnaire. The result shows that about half of workplaces of participants noticed increase in number of foreign employees, and most of them have experienced communication difficulties caused by lack of language skill, cultural difference in working style and lack of awareness toward different culture. Cultural diversity of workforces can create competitive advantage if it is valued and managed well. Organizations should offer supports to improve foreign employees’ language skill and local employees’ cultural awareness, as well as to make sure communication environment is well established.